Co‐expression of EGFR and MET has a synergistic effect on the prognosis of patients with oral squamous cell carcinoma. (9th December 2019) - Yokokawa, Misaki; Morita, Kei‐ichi; Oikawa, Yu; Kayamori, Kou; Sakamoto, Kei; Ikeda, Tohru; Harada, Hiroyuki
Abstract: Background: This study aimed to elucidate the correlation between gene amplification, protein expression of receptor tyrosine kinase, and prognosis of patients with oral squamous cell carcinoma (OSCC) using immunohistochemistry (IHC) and next‐generation sequencing data. Methods: We evaluated data pertaining to 208 patients with OSCC using IHC for epidermal growth factor receptor (EGFR) and mesenchymal‐epithelial transition factor (MET). Results: High expressions of EGFR and MET were detected in 60 and 41 patients, respectively. We evaluated the association of clinicopathological variables with high expressions of EGFR and/or MET. Distant metastasis was found in 9 of 41 patients (22.0%) and 6 of 15 patients (40.0%) with high expression of MET and high co‐expressions of EGFR and MET, respectively; statistically significant differences were detected in both high expression of MET ( P = .003) and high co‐expressions of EGFR and MET ( P = 3.41 × 10 −5 ). The cumulative 5‐year survival rate of patients with high and low expressions of EGFR or MET was approximately 65% and 85%, respectively. Conversely, among cases with high expressions of EGFR or MET, there was no additional decrease in the survival rate of patients harboring TP53 mutations. Moreover, the survival rate of patients with high co‐expression of both EGFR and MET was very poor (22.0%) ( P < 1.0 × 10 −9 ). Conclusion: Our findings suggest that evaluation of protein expressions of EGFR and MET may facilitate prognostic assessment of patients with OSCC; in addition, patients with OSCC should be screened for enrollment in clinical trials of combination therapy with EGFR and MET inhibitors.